Outcome Variation of CO 2 Laser and MicrodrillAssisted Stapedotomy in Otosclerosis (Bangladesh Journal of Otorhinolaryngology, 2024)
Background: CO2 laser and microdrill-assisted stapedotomy are widely performed procedures in otolaryngology practice. However, definite information regarding surgical advances, postoperative results, complications and how and in which patients these surgical techniques should be exclusively used is a source of continuous discussion.Aim: To compare the outcome of CO2 laser and microdrill-assisted stapedotomy in patients with otosclerosis.Methodology: We enrolled 26 cases as study sample on the basis of selection criteria. All these patients were evaluated by a complete clinical head and neck examination, preoperative oto-microscopic evaluation,pure tone audiometry (PTA) and a high-resolution CT scan.One group of patientswere treated by CO2 laser stapedotomy, and another group by microdrill-assisted stapedotomy. Fisher’s Exact test and Student’s t-test were done as appropriate, and a p-value 90%. In present study, 8(61.5%) and 9(69.2%) of the study subjects presented with tinnitus in the CO2 and Microdrill groups, respectively. 1(7.7%) and 1(7.7%) of the study subjects presented with dizziness in both groups, respectively. At 3 months postoperative follow-up, only 1(7.7%) case in the CO 2 laser group and 4(30.8%) cases in the Microdrill group developed complications. Among them, 1 (7.7%) and 2(15.4%) cases developed permanent vertigo in CO2 and Microdrill groups, respectively. 1(7.7%) case developed chorda tympani injury, and 1(7.7%) case developed worsened tinnitus in the Microdrill group. No significant (p>0.05) difference was observed between the groups regarding postoperative complications at 3 months.Conclusion: After analyzing the results of the present study, it can be concluded that there is no significant difference between CO2 laser and microdrill-assisted stapedotomy in terms of hearing outcome and complication. Bangladesh J Otorhinolaryngology 2024; 30(1): 15-23